Medicine Students’ Opinions on the English Discipline. University Polyclinic "Fabio Di Celmo" - Maira Pérez Pérez; Geisi Fernández Gómez; Isabel del Rosario Bagattín Martínez; Ditza Viera Álvarez; Maicel Eugenio Monzón Pérez (Medisur)
Background: The present century has been characterized by a predominance of English as the only international language for medicine and science. This statement is supported by the fact that knowledge of this foreign language completes the formation of a well prepared and highly competitive graduate student. Objective: To assess the views of medicine students on the study of English as a subject in their course. Methods: A cross-sectional descriptive study, conducted during the 2009-2010 academic year that included a sample of 26 medicine students of the University Polyclinic "Fabio Di Celmo". Variables that were considered: the actual need to teach English, students’ major motivations and satisfaction level with the educational process. Results: Most students (84.6%) considered it necessary to study English as part of the Medicine career. The most important motivation for its study was communication with English speaking patients, followed by the interest to consult technical literature (72.7% and 13.6% respectively). Teaching quality was assessed as excellent by almost all of the students (92.3%). Conclusions: Medical students of the University Polyclinic "Fabio Di Celmo" consider it necessary to study English, since it strongly supports their professional performance.